NF-κB activation induced by T cell receptor/CD28 costimulation is mediated by protein kinase C-θ - Coudronniere, Nolwenn (The National Academy of Sciences, 2000)
Protein kinase C-θ (PKCθ) is a Ca(2+)-independent member of the PKC family that is selectively expressed in skeletal muscle and T lymphocytes and plays an important role in T cell activation. However, the molecular basis for the important functions of PKCθ in T cells and the manner in which it becomes coupled to the T cell receptor-signaling machinery are unknown. We addressed the functional relationship between PKCθ and CD28 costimulation, which plays an essential role in T cell receptor-mediated IL-2 production. Here, we provide evidence that PKCθ is functionally coupled to CD28 costimulation by virtue of its selective ability to activate the CD28RE/activator protein-1 (AP-1) element in the IL-2 gene promoter. First, CD28 costimulation enhanced the membrane translocation and catalytic activation of PKCθ. Second, among several PKC isoforms, PKCθ was the only one capable of activating NF-κB or CD28RE/AP-1 reporters in T cells (but not in 293T cells). Third, wild-type PKCθ synergized with CD28/CD3 signals to activate CD28RE/AP-1. In addition, PKCθ selectively synergized with Tat to activate a CD28RE/AP-1 reporter. Fourth, CD3/CD28-induced CD28RE/AP-1 activation and NF-κB nuclear translocation were blocked by a selective PKCθ inhibitor. Last, PKCθ-mediated activation of the same reporter was inhibited by the proteasome inhibitor MG132 (which blocks IκB degradation) and was found to involve IκB-kinase β. These findings identify a unique PKCθ-mediated pathway for the costimulatory action of CD28, which involves activation of the IκB-kinase β/IκB/NF-κB-signaling cascade.